2011
DOI: 10.1186/1471-2458-11-530
|View full text |Cite
|
Sign up to set email alerts
|

'Pregnancy comes accidentally - like it did with me':reproductive decisions among women on ART and their partners in rural Uganda

Abstract: BackgroundAs highly active antiretroviral therapy (ART) restores health, fertility and sexual activity among HIV-infected adults, understanding how ART influences reproductive desires and decisions could inform interventions to reduce sexual and vertical HIV transmission risk.MethodsWe performed a qualitative sub-study among a Ugandan cohort of 1,000 adults on ART with four purposively selected categories of participants: pregnant, not pregnant, delivered, and aborted. In-depth interviews examined relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 25 publications
2
57
0
Order By: Relevance
“…[20] We recognize that behavioral response by HIV-positive women would be expected to depend on their knowledge of HIV status. [16] However, an examination of the interaction between HIV status and knowledge of status provided no evidence that this was significant.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] We recognize that behavioral response by HIV-positive women would be expected to depend on their knowledge of HIV status. [16] However, an examination of the interaction between HIV status and knowledge of status provided no evidence that this was significant.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…[17,18,3] In particular, a multi-country analysis of Demographic and Health Survey (DHS) data from nine countries revealed lower contraceptive uptake among HIV-positive women with prior knowledge of their status than counterparts who were HIV-negative in three of the countries included in the study: Zimbabwe, Kenya, and Malawi. [16] The apparent disconnect between fertility desire and contraceptive uptake among HIV-positive women has been attributed to diverse factors ranging from social desirability or stigma surrounding childbearing for HIV-positive individuals [19] to low contraceptive use among HIV-positive women based on the perception that they and their partners were infertile due to HIV infection [20]. Despite the general association between HIV-positive status and low fertility intention, perceived risk or uncertainly about HIV status have both been linked to desires to accelerate childbearing.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the risk of mother to child transmission of HIV, significant proportion of parents living with HIV continued to desire to have children [5][6][7][8]. Studies also revealed that HIV-positive women encountered unintended pregnancies with associated risk of mother to child transmission of HIV [9][10][11]. The experience of repeated untended pregnancy among HIV positive women particularly adolescents is partially due to inconsistence use of contraceptives [12].…”
Section: Introductionmentioning
confidence: 99%
“…This desire is often fueled by the strong societal and traditional values attached to parenthood in sub-Saharan Africa and is further enhanced by the development of increasingly effective antiretroviral regimens to reduce the risk of HIV transmission from an infected mother to her newborn or breastfeeding child.The success of highly active antiretroviral therapy (HAART) in reducing morbidity and mortality from HIV/ AIDS has been widely documented. Consequently, many HIV-infected persons are now living longer, healthier, and more productive lives.The infection rate among pregnant women in Sub-Saharan Africa is also alarmingly high, where 90% of global new child infections through mother-to-child transmission (MTCT) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%